Three dimensional (3D) histology in daily routine: practical implementation and its evaluation. (29th October 2014) - Carola Eberle, Franziska; Kanyildiz, Mukaddes; Maria Schnabl, Saskia; Schulz, Claudia; Häfner, Hans‐Martin; Adam, Patrick; Breuninger, Helmut
Summary Background The continuous evaluation of the edges of a tumor by means of three‐dimensional (3D) histology often appears complicated and require the surgeon and dermatopathologist to work together closely. We present clear rules that allow communication between all parties involved and then verify their application in daily routine. Methods Tissue processing, interpretation of results, as well as communication between the surgeon and the dermatopathologist are based on an algorithm with the aid of exact times and embedding cassettes, which allow precise topographic orientation. We evaluated the use of this method in daily clinic practice, taking into account 947 operated basal cell carcinomas in regard to the development of recurrent tumors. Results At a median follow‐up of 47 months, 10 of the 947 operated basal cell carcinomas (1.1 %) recurred. Sclerodermiform basal cell carcinomas and basal cell carcinomas which could not be curatively resected (R0 resection) during the initial surgery showed a significantly higher recurrence rate (p < 0.05 and p < 0.001). Conclusions Standardized rules for dealing with excised tissue allow an effective application of 3D histology in daily clinical practice. 3D histology results in low recurrence rates. Sclerodermiform basal cell carcinomas which could not be curatively resected (R0 resection) were identified as a risk group for the development of recurrent tumors.